Orthorexia Nervosa and Muscle Dysmorphia as Emerging Mental Health Threats in Athletes: A Comprehensive Narrative Review - Bojanowska, Hanna; Łuczyńska, Gabriela; Banatkiewicz, Joanna; Deka, Emilia; Domińczak, Jan; Dobosz, Adam; Bartkowska, Oliwia; Babik, Karolina; Czarnecka, Sofia; Wojnowski, Antoni (Journal of Education, Health and Sport, 2026)
Background: In modern sports, the line between healthy dedication and unhealthy obsession is becoming increasingly blurred. While classic eating disorders like anorexia and bulimia are well-known, Orthorexia Nervosa (ON) and Muscle Dysmorphia (MD) are growing problems that affect athletes of all genders but often go unnoticed. Objective: This review summarizes current knowledge regarding the prevalence, causes, and health consequences of ON and MD in athletes, based on literature acquired from PubMed, Embase, and Web of Science. Results: Evidence clearly shows that athletes are at a much higher risk for both conditions compared to the general population. Because strict diets and constant body monitoring are considered "normal" in sports, these disorders are often difficult to spot. Key risk factors include perfectionistic personality traits, pressure to meet weight requirements in certain sports, and the influence of social media, which promotes unrealistic body standards. Conclusion: Both ON and MD can lead to serious physical health issues, such as Relative Energy Deficiency in Sport (RED-S). Current findings highlight an urgent need for better screening tools designed specifically for athletes. Furthermore, a significant change in how we educate athletes and coaches about mental health and nutrition is necessary.